Prayer-marks Heralding Acute Coronary Syndrome (Journal of Health, Population and Nutrition, 2012)
DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9905 JHPN 2011; 29(6): 660 DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9905 JHPN 2011; 29(6): 660